PROTECTIVE EFFECTS OF BECLOMETHASONE AGAINST INSULIN INDUCED AIRWAY HYPER-REACTIVITY IN GUINEA PIG AND EXPLORATION OF ITS MECHANISM OF ACTION - Sharif, Mahjabeen; Khan, Bushra Tayyaba; Sharif, Mubashir (Journal of Ayub Medical College Abbottabad, 2014)
Background: Inhalational insulin was withdrawn from market in 2007 due to its potential to produce airway hyper-reactivity and bronchoconstriction. So we explored the possible mechanism underlying the acute contractile effects of insulin and protective effects of beclomethasone against insulin induced airway hyper-responsiveness on isolated tracheal smooth muscle of guinea pig in vitro. Methods: This was a laboratory based experimental study. Effects of increasing concentrations of histamine (10-8-10-3 M ), insulin (10-8-10-3 M), insulin pretreated with fixed concentration of indomethacin (10-6 M), and beclomethasone (10-6 M), were studied on isolated tracheal tissue of guinea pig in vitro by constructing cumulative concentration response curves. The tracheal smooth muscle contractions were recorded with Transducer on Four Channel Oscillograph. Results: Histamine and insulin produced a concentration dependent reversible contraction of isolated tracheal muscle of guinea pig. The mean±SEM of maximum amplitudes of contraction with histamine, insulin and insulin pretreated with indomethacin and beclomethasone were 92.5±1.20 mm, 35±1.13 mm, 14.55±0.62 mm and 22±1.154 mm respectively. Beclomethasone shifted the concentration response curve of insulin to the right and downwards. Conclusion: Beclomethasone significantly inhibited the contractile response of insulin which was presumably prostaglandin mediated. So pretreatment of inhaled insulin with beclomethasone may have clinical implication in amelioration of its potential respiratory adverse effects such as bronchoconstriction. Keywords: Histamine, Inhaled insulin, Beclomethasone, Oscillograph, Tracheal muscle